Logic and its applications 4th Indian Conference, ICLA 2011, Delhi, India, January 5-11, 2011. Proceedings - Banerjee, Mohua; Seth, Anil 1965- (Lecture Notes in Computer Science, 2011)
Edited in collaboration with FoLLI, the Association of Logic, Language and Information, this book constitutes the refereed proceedings of the 4th Indian Conference on Logic and Its Applications, ICLA 2011, held in Delhi, India, in January 2011. The 14 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 34 submissions. The papers present current research in all aspects of formal logic ranging from pure and applied logic to history of logic.